WHAT INFLUENCES INDUSTRIAL CLIMATE IN INDONESIA? – A QUALITATIVE STUDY - Faisal, M.; Maarif, Syamsul; Fahmi, Idqan; Yulianto, Budi; Dwidienawati, Diena (CENTRAL ASIA AND THE CAUCASUS, 2022)
Organizations worldwide have experienced how workplace disputes have resulted in negative impacts on all related stakeholders. To organization, the impacts can be in the term of revenue loss, the destruction of the company assets, and sometimes it can cause lives[1]. Favorable workplace environment has also been reported to influence the individual level of job performance[2]. Conflict raised by unfavorable workplace climates can reduce organization productivity and affect the chance of organization survival[3]. In the opposite side, research has shown that an organization's Industrial Relations (IR) climate relates to productivity, efficiency, general employee satisfaction, union loyalty, and organizational commitment[4]. [5]proved that the industrial relations climate can improve performance at the individual employee level. Higher economic competition strengthens the need to foster a good IR climate. There is a need to establish a better organizational flexibility to establish a good workplace relation to ensure commitment among workers[3].